Knowledge and Practice on Selected Aspects of Postnatal Care Among Postnatal Mothers - Pradan, A; Rani, U (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Maternal mortality is higher in women living in rural areas and among poorer communities. Young adolescents face a higher risk of complications and death as a result of pregnancy than other women. Skilled care before, during and after childbirth can save the lives of women and newborn babies. Only a small proportion of women in developing countries- less than 30% receive adequate postpartum care. In very poor countries and regions as few as 5% of who receive such care. A large proportion of maternal deaths occur during the first 6 weeks after delivery, and postpartum care might help to prevent many of these deaths. In developed countries, 90% of new mothers receive postpartum care. MATERIALS & METHODS: A descriptive approach with descriptive correlation research design was used to assess the knowledge and practice on selected aspects of postnatal care among postnatal mothers. The study was carried out in Banashankari Referral Hospital, Bangalore. The purposive sampling technique was used to select the 60 samples of postnatal mothers. The collected data were analyzed by using descriptive and inferential statistics. RESULTS: Thirty Three (55%) respondents were having moderately adequate knowledge regarding selected aspects of postnatal care, 24(40%) were having inadequate knowledge and only 03(05%) of respondents had adequate knowledge out of 60 samples . The level of practice was out of 60 respondents, 29(48.33%) respondents were having inadequate practices, 26(43.33%) were having moderately adequate practices and only 05(08.34%) of them had adequate practices on selected aspects of postnatal care. CONCLUSION: The findings of the study conclude that the postnatal mothers had moderately adequate knowledge and practices on selected aspects of postnatal care. The study suggests that the postnatal mothers require educational instructions for improving the knowledge and practice. BACKGROUND: Early diagnosis and emergent surgical management of perforation peritonitis remain the mainstay of treatment. The aim of study was to find the effect of early surgery on postoperative outcome in patients with perforation peritonitis. MATERIALS & METHODS: A retrospective medical report of 200 patients who underwent exploratory laparotomy and proceed for perforation peritonitis from July 2015 to December 2016 was studied. Patients were divided into two groups based on the time of surgery i.e: Early (<6 hours) and late (≥6 hours) intervention groups. All perioperative outcome of surgery were analyzed. RESULTS: Late intervention patients were more likely to develop complications (34.3 and 17.8%, P < 0.05) and mortality (14 and 6%, P<0.05) in comparison to early intervention patients and had significantly higher median time to resumption of normal diet (5and 2.8 days, length of hospital stay (15 and 9 days) and length of ICU stay (8 and 4 days) (P < 0.05). The time to operation (≥ 6 hours) and preoperative hypotension were independent risk factors for postoperative complications in multivariate analysis. CONCLUSION: Early surgical intervention within six hours along with broad spectrum antibiotics preceded by adequate aggressive resuscitation improves postoperative outcomes in perforation peritonitis. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, page: 37-41